Pengaruh Religiusitas, Kepercayaan dan Kesenangan Terhadap Niat Untuk Menggunakan Aplikasi Perhitungan Zakat - Masradin Masradin; Mursalim Laekkeng; Nur Wahyuni (Al-Buhuts, 2023)
This research was conducted to determine the influence of religion, belief and pleasure on the intention to use the Zakat Calculation Application. Using primary data through a questionnaire as many as 170 respondents with criteria 1) are Muslim, 2) Have a job/income, 3) Have never used a zakat calculation application but are familiar with the zakat calculation application. Data were analyzed using the SPSS 26 program. The results of this study indicate that: (1) the effect of religiosity on the intention to use the zakat calculation application is positive but not significant; (2) Belief in the intention to use the zakat calculation application has a significant positive result; (3) Pleasure with the intention of using the zakat calculation application, the negative results are not significant. This research gives the meaning that even though someone has an appreciation of his religious teachings, it is not necessarily able to influence his intention to choose a zakat calculation application. The existence of responses and application updates carried out by the carrier is able to arouse one's self-confidence so that it encourages the intention to use the zakat calculation application. The ease of technology for the application of zakat calculations has not been able to generate a feeling of pleasure because what is expected is that the application must be able to show the legal basis for determining zakat which is used as a reference for consideration